1998
DOI: 10.1192/pb.22.6.354
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of respite needs for carers of persons with severe mental illness

Abstract: Respite needs for carers of persons with severe mental illness were assessed using a semi-structured inverview. Very few carers were currently using respite facilities. The need for respite was widespread, although largely unmet. Carers shared clear and definite ideas concerning the layout of a good respite service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 5 publications
3
9
0
2
Order By: Relevance
“…The findings confirm other research on respite care services with regard to: the lack of services available for mental health consumers and their carers (Carers NSW 2002; Malcolm et al . 1998; SANE Australia 1998b; Twigg & Atkin 1994); the poor quality of services and the negative impact this has on both carers and care recipients, the importance of understanding care recipients’ experience with and attitudes towards respite care (Ashworth & Baker 2000; Hanson et al .…”
Section: Discussionsupporting
confidence: 89%
“…The findings confirm other research on respite care services with regard to: the lack of services available for mental health consumers and their carers (Carers NSW 2002; Malcolm et al . 1998; SANE Australia 1998b; Twigg & Atkin 1994); the poor quality of services and the negative impact this has on both carers and care recipients, the importance of understanding care recipients’ experience with and attitudes towards respite care (Ashworth & Baker 2000; Hanson et al .…”
Section: Discussionsupporting
confidence: 89%
“…It may be that cohabiting family carers perceive less of a need for health and community services to provide such care, given their significant role in providing care generally. Previous research has suggested that cohabitating carers may decline the offer of various forms of care due to a perception that this may negatively impact on their being the primary caregiver (Harris, Diminic, Marshall, Stockings, & Degenhardt, 2015;Malcolm, Rowlands, & Inch, 1998). This remains speculative and other possibilities could have led to this result.…”
Section: Discussionmentioning
confidence: 49%
“…One such study indicated that 27% of carers expressed a need for professional support with their caring responsibilities that was not being met 47 . Another found that, of 63% of carers reporting a need for day care respite, only one‐third had their needs met through respite care services 48 …”
Section: Discussionmentioning
confidence: 99%
“…An international review of the literature on respite care among such carers indicates that a broader range of barriers (encompassing other factors such as quality of care, stigma and attitudes, and self‐awareness) contribute to under‐utilisation of respite services 55 . Some carers have expressed feeling resigned to their caring role, have given up hope for further assistance, and feel that little can be done to help them 47,48 . Issues regarding loss of control over decisions regarding treatment if a ‘professional’ is involved in the caring process have also been identified 48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation